Water availability and water usage solutions for electrolysis in hydrogen production. (15th September 2021) - Simoes, Sofia G.; Catarino, Justina; Picado, Ana; Lopes, Tiago F.; di Berardino, Santino; Amorim, Filipa; Gírio, Francisco; Rangel, C.M.; Ponce de Leão, Teresa
Abstract: Europe is committed to a new growth strategy with no net greenhouse gases emissions by 2050, where hydrogen has a clear role to play. Portugal's strategy for H2 sets public policies promoting an industry focused on the hydrogen value chain. Considering the production of green hydrogen from renewable sources is key, water electrolysis becomes a priority, and with it, the need to assess the suitability of water sources, which is determined by both quantitative and qualitative factors. This work presents a new approach to assess the suitability of water sources for hydrogen production via water electrolysis by applying a Sustainable Value Methodology for decision-making support, combining economic, environmental and social criteria. The approach is applied to two different sites in Portugal: a semi-urban location on the Atlantic coast (site A) and a rural area far from the coast (site B). For both sites, water sources are evaluated regarding water availability, quality, transport options, abstraction costs, treatment needs and regulation (including environmental constraints) and social acceptance. The resulting sustainable value indicator, aggregator of different levels of information, enables a relative quantitative comparison of the performance of different water sources for electrolysis and the involved costs. It is found that the public grid water is the most suited source of water for electrolysis due to lower risk of supply, lower costs and avoids complex permitting processes. Likewise, seawater and wastewater treatment plant effluent (only in site A) showed to be possible water sources where the factors most affecting suitability are transport costs for water and waste disposal from water treatment. Graphical abstract: Image 1 Highlights: Assessment of water sources suitability using a sustainable value approach. Green H2 produced from water electrolysis is crucial to decarbonise Europe. Identification and characterization of typified water sources to produce H2 . Public water showed to be the most suited source for electrolysis for the two sites. Seawater and reused waters maybe considered for lower transport/treatment costs.